"When my worse fear happened": Mental health nurses' responses to the death of a client through suicide. Issue 5 (9th May 2021) - Morrissey, Jean; Higgins, Agnes
Accessible Summary: What is known on the subject?: The death of a client to suicide evokes a range of grief responses for mental health nurses (MHNs), which vary in intensity according to the nature of the therapeutic relationship with the deceased client. There are limited qualitative studies on the experiences of nurses working in the community and the personal or professional strategies used by nurses to cope with the death of a client by suicide. What this paper adds to existing knowledge?: Following a client suicide, MHNs were often left to carry the burden of grief alone and to care for themselves with the support of their family and colleagues. While all participants perceived the need for support following the death of a client by suicide, they were offered minimal support beyond the debriefing meetings, with their grief experience being largely unacknowledged and disenfranchised. What are the implications for practice?: MHNs and services need to establish and promote a culture of openness in which suicide is anticipated as a possible outcome, even with excellent standards of care and wherein all staff are supported and encouraged to discuss and reflect on their concerns and fears during the aftermath of a client suicide. As MHNs are often left to carry the burden of grief alone, services need to recognize the emotional cost of embodied engagement with clients and families and provide the necessary supports. Abstract: Introduction: Experiencing a client's death through suicide is complex and challenging, yet limited research exists on how MHNs might deal with its aftermath. Aim: This study aimed to explore the impact and responses of MHNs to a client suicide. Method: The study design is a secondary analysis of an existing data set involving semi‐structured interview with 33 MHNs that were analysed using the principles of grounded theory. To answer the secondary question on the impact and responses of MHNs to the death of a client by suicide a subset of the data from 10 participants who experienced the death of a client by suicide were re‐analysed using thematic analysis. Ethical approval was granted by the university ethics committee. Findings: The findings identified five themes: "Hearing the news, " "Experiencing the impact of grief, " "Grieving privately" "Searching for meaning" and "Questioning practice." Discussion: Findings highlighted that although participants perceived the need for support, they were offered minimal support beyond the debriefing meetings, with their grief experience being largely unacknowledged and disenfranchised. Implications for practice: MHN services need to promote a culture of openness wherein all MHNs are supported and encouraged to discuss their concerns and fears during the aftermath of a client suicide.